2005
DOI: 10.2320/matertrans.46.337
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis of Cation Selective Cr-goethite as Protective Rust of Weathering Steel

Abstract: We have performed extended X-ray absorption fine structure (EXAFS) analysis for artificial Cr-goethite to elucidate the local structure around Cr in Cr-goethite. The spectra were obtained using synchrotron radiation X-rays at the Photon Factory in Tsukuba. The first shell contributions were isolated by Fourier filtering the EXAFS data, and the inverse Fourier transformed single-shell data were analyzed using a curve fitting method. The results show that Cr is coordinated with (7 AE 1) O 2À ions. The protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
0
20
1
3
Order By: Relevance
“…21) The fundamental shape of the observed spectra indicates that akaganéite is contained in the rust samples. Additionally, the shoulder peak on the main absorption edge reveals the presence of the other chlorides in the rust samples.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…21) The fundamental shape of the observed spectra indicates that akaganéite is contained in the rust samples. Additionally, the shoulder peak on the main absorption edge reveals the presence of the other chlorides in the rust samples.…”
Section: àmentioning
confidence: 99%
“…The others and akaganéite were used in the Cl K-XANES study. In the previous Cl K-XANES study, 21) we observed the spectra of MgCl 2 (another major component of seawater), NaClO 2 (relatively stable chlorate), FeCl 3 , CrCl 3 and CrCl 3 Á6H 2 O (well-known metal chlorides).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The effect of nickel on the structure of iron oxyhydroxides and oxides should be further studied, although some models of the effect of nickel on the rust formed by chloride ions were proposed. 20,21) …”
Section: Characterizations Of Particlesmentioning
confidence: 99%
“…Actually, the addition of nickel seems to influence the structure of rust formed on their surface and especially brings the formation of the protective rust layer in a Cl-rich environment. 20,21) In addition, it has been reported that the unit cell dimensions of -FeOOH change slightly by the addition of nickel. 22) However, the role of nickel in the transformation of GR2(SO 4 2À ) into the iron oxyhydroxides and oxides in SO 4 2À -environment is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been many analyses of rust on the steels in mild environments, [3][4][5][6][7][8][9][10] there are many problems that remain unclear regarding the basic mechanisms of the rust formation 11) and the effect of alloy elements [12][13][14] in saline environments. Therefore, in order to obtain the corrosion guidance for weathering steels that can be used in coastal environment, the thermodynamic stability of various rusts (Fe-X system) was investigated using a binary-phase potential-pH diagram.…”
Section: Introductionmentioning
confidence: 99%